Mitotic and meiotic chromosomes of Artemia (Branchiopoda) from populations of La Pampa Province, Argentina - Rodríguez Gil, S. (1998)
Three populations of Artemia from La Pampa Province, Argentina, were cytogenetically analyzed: Salinas Grandes de Hidalgo, Laguna Callaqueo, and Laguna Colorada Chica. Both mitotic and male meiotic chromosomes were studied. All 3 populations share the same diploid (2n = 44) and/or haploid chromosome number (n = 22), and hence were determined as Anemia persimilis Piccinelli and Prosdocimi. Although bivalents decrease gradually in size, differences among the larger and the smaller ones were apparent. So far, no cytogenetic differences have been detected among the 3 populations. Chromosomes with metacentric, submetacentric, and telocentric morphology were detected in mitotic prometaphase cells, suggesting that chromosomes of Anemia may be monocentric.